Tubulin and microtubules as molecular targets for ttfield therapy - Kalra, Aarat P.; Patel, Sahil D.; Bhuiyan, Asadullah; Rezania, Vahid; Lewis, John; Shankar, Karthik; Tuszynski, Jack A. (My University, 2019)
TTField (Tumor-treating field) therapy utilizes low intensity intermediate frequency AC electric fields to reduce the spread of cancer. While it has attained FDA approval for the treatment of recurrent glioblastoma multiforme, the exact molecular targets of TTField therapy are not well understood. Microtubules are pipe-like polymers of the highly charged (–31 e) and strongly dipolar (dipole moment 1666 D) protein, α, β- tubulin. Studies on the electrical properties of microtubules have recently gained interest, with them being modelled as molecular targets of TTFields. Here, we experimentally show that while tubulin polymerized into microtubules leads to an increase in solution capacitance, unpolymerized tubulin has no appreciable effect. To the best of our knowledge, we present the first experimental quantification of the capacitance of a 20 μm-long microtubule. Using these results, we calculate the resonant frequency of a microtubule meshwork in a cell-like environment to be in the TTField regime. Our results utilize high ionic strength solutions and cell-like concentrations of tubulin to show the potential of microtubules as the targets of TTField action and as intracellular charge-storage devices. We conclude with a hypothesis of an electrically-tunable cell, where the dielectric properties of the cytoskeleton alter local and global charge storage and transport.
Keywords: cancer; tumor-treating fields therapy; neoplasms; ribosomal; microtubules; recombinant DNA